2019
DOI: 10.3390/molecules24040787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epigallocatechin Gallate on the Stability of Epicatechin in a Photolytic Process

Abstract: Catechins belonging to polyhydroxylated polyphenols are the primary compounds found in green tea. They are associated with many physiological properties. Epicatechin (EC) is a non-gallate-type catechin with four phenolic hydroxyl groups attached. The changes in EC treated with color light illumination in an alkaline condition were investigated by chromatographic and mass analyses in this study. In particular, the superoxide anion radical (O2•−) was investigated during the EC photolytic process. EC is unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
(63 reference statements)
0
23
0
1
Order By: Relevance
“…The generated can reduce NBT to form formazan, which can be detected at 560 nm. It has also been reported that catechin hydrate or epicatechin treated with BLI at 20 W/m 2 for 0–60 min generates by the NBT reduction method [ 5 , 15 ]. The effects of AlCl 3 on the generation of from the photolytic process of catechin were investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The generated can reduce NBT to form formazan, which can be detected at 560 nm. It has also been reported that catechin hydrate or epicatechin treated with BLI at 20 W/m 2 for 0–60 min generates by the NBT reduction method [ 5 , 15 ]. The effects of AlCl 3 on the generation of from the photolytic process of catechin were investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The depolymerization of BtPA via photooxidation in total chemical reactions by aluminum ion catalysis is represented in Equation (8) [ 46 , 49 ]. Subsequently, the carbocation ( Figure 10 H) can be reduced to generate catechin at m / z 289 ( Figure 10 A) [ 5 , 15 , 48 ]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shishido et al showed that when catechin is illuminated with ultraviolet A at 400 nm, its pro-oxidative mode is related to the formation of reactive oxygen species (ROS), as shown by an electron paramagnetic resonance (EPR) spin-trapping technique [23]. Under BLI and basic conditions, catechin forms a B-type proanthocyanidin, and O •− 2 is generated by photosensitized oxidation in a photolytic reaction and with the dimeric catechin at m/z 577 in a condensation reaction [4,24]. The proposed scheme for the photolysis of catechin is shown in Figure 2.…”
Section: Proposed Photoreaction Mechanism For Catechinmentioning
confidence: 99%